16. Risk of fall and related factors in osteoporosis patients at the National Geriatric Hospital - Anh, Trinh Ngoc; Luc, Tran Viet; Hue, Do Thi Thu; Tam, Nguyen Ngoc; Huyen, Vu Thi Thanh (Tạp chí Nghiên cứu Y học, 2023)
This study was conducted to assess the association between risk of fall and relating factors in osteoporosis patients at the National Geriatrics Hospital. This is a cross-sectional study on 141 osteoporotic patients aged ≥ 60 years old examined or treated at the National Geriatric Hospital. Data were collected by using designed tools including characteristics of these patients. We entered data on Redcap and used SPSS version 22.0 for analysis. The mean age and standard deviation were 73.12 (8.62) with female patients accounted for majority with 94.3%. The mean age of patients with high risk of falls was higher than patients with low risk of falling (with p < 0.05). Heart failure and diabetes mellitus were associated with the risk of falls in older patients with osteoporosis (p < 0.05). The mean Charlson Index and mean number of diseases in the group of patients at high risk of falls were higher than in the group of patients with low risk of falls (with p < 0.05). The study showed that advanced age, heart failure, diabetes, and depression were significantly associated with a higher risk of falls in older patients with osteoporosis.